Under a Non-Existent Commemorative Plaque: The 84th Anniversary of the Introduction of the Ghetto Bench at the University of Warsaw – A Speech Delivered at the Ceremony Organized by the Student Antifascist Committee in the Courtyard of the University of Warsaw on October 5, 2021 - Elżbieta Janicka (Studia Litteraria et Historica, 2021)
The ghetto bench (1937) is emblematic of the process by which anti-Semitism was legalized and institutionalized in the interwar Republic of Poland (1918–1939). This text focuses on the failure to include this knowledge in the mainstream narrative, a problem which continues to this day. The lack of an integrated history results from a lack of condemnation, and from the fact that the dominant majority has not broken away from the framework of assumptions of concealed processes and events. After 1989, these assumptions have been additionally celebrated in the cult of interwar Polish statehood. The collision of the Polish dominant culture with the liberal-democratic formal-legal framework produced the collapse of liberal democracy in Poland (2015). This text thus questions the location of the ghetto bench and its cultural representations in the field of memory studies. By pointing to the current stakes of the discourse on Polish anti-Semitism, the author calls for a revision of socio-cultural norms which means socio-cultural change.